Criopreservação do plasma rico em plaquetas (PRP) de equinos - Kwirant, Liomara Andressa do Amaral (2013)
Platelet-rich plasma (PRP) is defined as a plasma volume with a higher platelet count than that of whole blood. PRP has been widely used for treatment of different lesions, both in human and in veterinary medicine. The aim of this study was to search for an effective method of storing equine PRP, without loss of viability. Blood (500 ml) was collected from 8 clinically healthy ponies, where 100 ml were used to prepare PRP; 2 ml were used to determine platelet count and mean platelet volume (MPV). Whole blood was centrifuged at 1000 rpm for 10 minutes to obtain plasma. The plasma obtained was centrifuged again at 1400rpm for 10 minutes to obtain 10 ml of PRP. PRP was divided into 3 samples of 2 ml, one being considered the fresh sample and the other 2 were frozen. Platelet count, determination of MPV and morphological evaluation were performed on the fresh sample. Morphologic evaluation consisted of counting 200 platelets under light-microscopy and their classification in inactive (discoid), activated (with pseudopodia) or uncertain state (who lost the discoid form but showed no pseudopodia). The samples to be cryopreserved were stored in a freezer at -80 ° C for 14 days, containing 6% dimethyl sulfoxide (DMSO) as a cryoprotectant or without any addition of cryoprotectants. After this period, samples were thawed and submitted to the same analysis of the fresh sample. The fresh and DMSO frozen samples showed no difference in the total number of platelets, activated platelets and MPV (617.9 ± 65.5 x103/μL, 5.3 ± 0.06 fL, 9.6%) However, samples frozen without DMSO showed fewer platelets (519.6 ± 66 x103/μL), higher MPV (5.71 ± 0.08 fL) and a higher percentage of activated platelets (13.87%). 6% DMSO proved be an effective cryoprotectant in storing equine PRP at -80°C for 14 days.